Orientation and Faulted Structure of [gamma]-Phases in Lanthanum-Alloyed Ni-Al-Cr Superalloy; AIP Conference Proceedings; Vol. 1909 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2017 (AMHS’17) - Nikonenko E. L. Elena Leonidovna; Shergaeva L. Lyubov; Popova N. Natalya; Koneva N. Nina; Rongshan Qin; Gromov V. Victor; Fedorischeva M. Marina (2017, 2017)
Title screen